Multilingual Memory of Migration - A Participatory Oral History Project in Austria - Traska, Georg (Revija za elementarno izobraževanje, 2024)
The article lays out the method of the participatory Oral History project “Multilingual Memory of Migration” against the political background of an unacknowledged Austrian migration history and the political paradigm of monolingualism. The participatory concept engages students in a research process of Austrian migration history, addressing especially (but not exclusively) students with an own migration and multilingual background to conduct intergenerational biographical interviews. By benefitting from the students’ language skills and community outreach, the project aims at creating a contribution to a national “archive of migration” as such not institu–tionalized in Austria.
Keywords: migration, multilingualism, participatory research, Oral History, intergenerational.